Endovascular Treatment for Variceal Hemorrhage: TIPS, BRTO, and Combined Approaches - Lipnik, Andrew J.; Pandhi, Mithil B.; Khabbaz, Ramzy C.; Gaba, Ron C. (Seminars in Interventional Radiology, 2018)
Variceal hemorrhage is a feared complication of portal hypertension, with high rates of morbidity and mortality. Optimal management requires a thoughtful, multidisciplinary approach. In cases of refractory or recurrent esophageal hemorrhage, endovascular approaches such as transjugular intrahepatic portosystemic shunt (TIPS) have a well-defined role. For hemorrhage related to gastric varices, the optimal treatment remains to be established; however, there is increasing adoption of balloon-occluded retrograde transvenous obliteration (BRTO). This article will review the concept, history, patient selection, basic technique, and outcomes for TIPS, BRTO, and combined TIPS + BRTO procedures for variceal hemorrhage.
Keywords: variceal hemorrhage; gastric varices; esophageal varices; transjugular intrahepatic portosystemic shunt; balloon-occluded retrograde transvenous obliteration